Outcomes of MIS-C patients treated with anakinra: a retrospective multicenter national study - Francesco Licciardi; Carlotta Covizzi; Marta Dellepiane; Nicole Olivini; Maria Vincenza Mastrolia; Andrea Lo Vecchio; Viviana Monno; Maria Tardi; Angela Mauro; Maria Alessio; Giovanni Filocamo; Marco Cattalini; et al. (Frontiers in Pediatrics, 2023)
BackgroundThe treatment of multisystem inflammatory syndrome in children unresponsive to first-line therapies (IVIG and/or steroids) is challenging. The effectiveness of IL-1 receptor antagonist, anakinra, is debated.Patients and methodsWe conducted an anonymous retrospective multicenter study on MIS-C patients treated with anakinra in Italy from January 2020 to February 2021. Our study outcomes included the percentage of patients who required further therapeutic step-up, the percentage of patients who experienced fever resolution within 24 h and a reduction of CRP by half within 48 h, and the percentage of patients who developed Coronary Artery Anomalies (CAA) during follow-up.Results35 cases of MIS-C were treated in 10 hospitals. Of these, 13 patients started anakinra while in the ICU, and 22 patients started anakinra in other wards. 25 patients (71.4%) were treated with corticosteroids at a starting dose 2–30 mg/Kg/day plus IVIG (2 g/Kg), 10 patients (28.6%) received only corticosteroids without IVIG. Anakinra was administered intravenously to all patients in Group A (mean dose 8 mg/Kg/day), and subcutaneously in Group B (mean dose 4 mg/Kg/day). Only two patients required further treatment step-up and no patients developed CAA after receiving anakinra. The most commonly observed side effect was an increase in ALT, occurring in 17.1% of patients.ConclusionsIn this retrospective cohort of severe MIS-C patients treated with anakinra we report favorable clinical outcomes with a low incidence of side effects. The simultaneous use of steroids ± IVIG in these patients hinders definitive conclusions regarding the need of IL-1 inhibition in MIS-C treatment.